The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1097/mcc.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Why do we fail to deliver evidence-based practice in critical care medicine?

Abstract: Purpose of review The use of evidence-based practices in clinical practice is frequently inadequate. Recent research has uncovered many barriers to the implementation of evidence-based practices in critical care medicine. Using a comprehensive conceptual framework, this review identifies and classifies the barriers to implementation of several major critical care evidence-based practices. Recent findings The many barriers that have been recently identified can be classified into domains of the consolidated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
0
13
0
1
Order By: Relevance
“…However, this study also showed the low frequency to equip the specific protocol in each ICU, or 50% or less, which could be considered as one of the major barriers to be managed regardless of the presence of COVID-19. As many studies successfully showed a pivotal role for implementation or introduction of ICU care, this simple, but not time-or resource-consuming approach could be a key stimulus and should be routine in the ICU to facilitate efficient implementation of evidence-based approaches to ICU care (12,16,37,38). Tele-medicine, which is getting public interest and recommended in several elements such as elements E (39) and F (37,40), could be also an alternative to promote implementation instead of strict regulations regarding infection control or family visits.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study also showed the low frequency to equip the specific protocol in each ICU, or 50% or less, which could be considered as one of the major barriers to be managed regardless of the presence of COVID-19. As many studies successfully showed a pivotal role for implementation or introduction of ICU care, this simple, but not time-or resource-consuming approach could be a key stimulus and should be routine in the ICU to facilitate efficient implementation of evidence-based approaches to ICU care (12,16,37,38). Tele-medicine, which is getting public interest and recommended in several elements such as elements E (39) and F (37,40), could be also an alternative to promote implementation instead of strict regulations regarding infection control or family visits.…”
Section: Discussionmentioning
confidence: 99%
“…There is still a significant gap in our understanding of how best to translate knowledge to practice in medicine, and we lack an effective framework for implementing clinical practice. Identified barriers to integration of evidence in the ICU include knowledge gaps, limited interdisciplinary collaboration, and complexity of care ( 47 ). Particularly in ARDS, the initial identification of ARDS is an important diagnostic step prior to initiating possible therapies ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, in vivo and ex vivo adult rat studies examining the impact of high V T without PEEP on surfactant and lung function also demonstrated an impaired lung compliance accompanied by increased total surfactant pools in BALF. Further analyses of BALF revealed an elevated SA/LA ratio and poor surfactant surface tension lowering properties (31,44,45). LAs represent the biophysically active form and consist of TM, LBL, ML, and MV surfactant structures.…”
Section: Discussionmentioning
confidence: 99%